2021
DOI: 10.1371/journal.pone.0256790
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial injury secondary to severe acute liver failure: A retrospective analysis supported by animal data

Abstract: To investigate whether acute liver failure (ALF) leads to secondary acute myocardial injury, 100 ALF patients that were retrospectively identified in a single center based on ICD 10 codes and 8 rats from an experimental study that died early after bile duct ligation (BDL) were examined. Creatine kinase (CK), creatine kinase-MB isoenzyme (CKMB) and cardiac troponin-I (cTnI) were analyzed as markers of myocardial injury. For histological analysis, hematoxylin-eosin (HE), elastic Van Gieson (EVG), CD41 and myelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Building upon these observations, our previous research has shown that major adverse cardiac events (MACE) are a critical determinant of mortality in ALF patients [11]. Furthermore, we hypothesized that inflammation, endothelial dysfunction, and direct bile acid signaling may be involved in the pathophysiology of secondary myocardial injury in ALF as we observed a dropout rate of 20% early after BDL in a previous study, some even with macroscopically visible infarcts [11].…”
Section: Introductionmentioning
confidence: 63%
“…Building upon these observations, our previous research has shown that major adverse cardiac events (MACE) are a critical determinant of mortality in ALF patients [11]. Furthermore, we hypothesized that inflammation, endothelial dysfunction, and direct bile acid signaling may be involved in the pathophysiology of secondary myocardial injury in ALF as we observed a dropout rate of 20% early after BDL in a previous study, some even with macroscopically visible infarcts [11].…”
Section: Introductionmentioning
confidence: 63%
“…Hepatocellular injury and elevated levels of various serological markers such as ALT, AST, TNF-α, YKL-40 (related to liver injury and inflammation) exacerbate hemodynamic disturbances and hyperdynamic circulation which further aggravate myocardial injury 13 , 35 , 43 . It was concluded that the degree of liver failure was positively correlated with myocardial injury in patients with cirrhosis 44 , 45 . This coincides with our results, in which liver failure and level of ALT were significantly different between the myocardial and non-myocardial injury groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular injury and elevated levels of various serological markers such as ALT, AST, TNF-α, YKL-40 (related to liver injury and in ammation) exacerbate hemodynamic disturbances and hyperdynamic circulation which further aggravate myocardial injury [12,18,23]. It was concluded that the degree of liver failure was positively correlated with myocardial injury in patients with cirrhosis [24]. Therefore, liver failure and liver-related biochemical indices including ALT and AST were considered as possible risk factors of myocardial injury in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%